Sequence dependent lipid-mediated effects modulate the dimerization of ErbB2 and its associative mutants - Prasanna, Xavier; Praveen, P. J.; Sengupta, Durba (Physical Chemistry Chemical Physics, 2013)
The association of transmembrane helices is an important event in several biological processes, but the factors governing association, especially the non-specific environmental effects, have still not been elucidated. Here, we use coarse-grain molecular dynamics simulations to study the association of ErbB2 transmembrane helices and three ``oncogenic mutants.'' Self-assembly simulations and the dimerization free-energy profiles confirm an energetically-favorable dimerized state for both the wildtype and the mutants. The dissociation free energy of all three mutants is calculated to be larger than the wildtype peptide. Along with favourable protein-protein interactions, non-specific environmental effects are observed to contribute to the association. In particular, local bilayer thinning along with membrane perturbations are seen around the mutants. The membrane perturbations are reduced upon helix association, suggesting that lipid chain packing is an important driving force for helix dimerization. Our results highlight the importance of both specific as well as non-specific driving forces in the association of transmembrane helices.